A amizade em crianças da educação infantil es relações interpessais estabelecidas no ambiente escolar - Lima, Priscila Saraiva de [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The research aims to propose a study of the central concepts of friendship among children of kindergarten and how such conceptions influence the interpersonal relationships within the school. We intend to observe the friendly relations between the kindergarten children, to examine how teachers of early childhood education business with the friendly relations between children and their conflicts and to propose alternatives to work with the theme friendship in the garden childhood, aiming at the socio-moral development of children. To do so, as the main theoretical basis the studies of Jean Piaget (1932/1994) on the development of moral reasoning in children. The methodology is based on Piaget's clinical method, which aims to understand how the subject thinks, analyze and resolve certain situations, presented as short stories. We hope that by doing so, we contribute to the debate on the educational work aimed at building the moral autonomy of the children, especially in kindergarten

A pesquisa que propomos tem como objetivo central um estudo sobre a amizade entre crianças da Educação Infantil e como esta influencia as relações interpessoais estabelecidas no ambiente escolar. Pretendemos observar as relações de amizade entre vinte e duas crianças da Educação Infantil, analisar o modo como os professores da lidam com as relações de amizade entre as crianças e seus conflitos e propor alternativas para se trabalhar com o tema “amizade” na Educação Infantil, objetivando o desenvolvimento sócio-moral das crianças. Para tanto, teremos como principal base teórica os estudos de Jean Piaget (1932/1994), sobre o desenvolvimento do juízo moral na criança. A metodologia foi baseada no método clínico piagetiano que tem como finalidade entender como o sujeito pensa, analisa e resolvem determinadas situações, apresentadas em forma de historietas. Esperamos que, ao proceder dessa forma, possamos contribuir para o debate acerca de trabalhos educativos voltados à construção da autonomia moral das crianças, sobretudo, na Educação Infantil
Keywords: Amizade; Autonomia nas crianças; Desenvolvimento moral; Educação de crianças; Relações humanas; Friendship; Autonomy in children; Moral development; Education; Interpersonal relations